Cognitive Linguistics Theory in Anthropocentric Paradigm - Muratkhodjayeva, Feruzakhon (International Journal of Industrial Engineering, Technology & Operations Management, 2024)
This study examines cognitive linguistics within the framework of the anthropocentric paradigm, focusing on the dynamic interplay between language and thought. The study aims to unravel how these two elements mutually shape and influence each other, highlighting the centrality of the anthropocentric perspective in understanding cognitive processes. The research underscores the relevance of this approach in contemporary linguistics, offering valuable insights into the ways in which language not only reflects but also molds our perception of reality. Through a detailed analysis, the study explores how linguistic structures inform cognitive frameworks and how these structures, in turn, guide thought patterns. The findings demonstrate that language is a key determinant in shaping cognitive processes and influencing how individuals conceptualize and engage with the world around them. The author's scientific contribution lies in advancing linguistic theories and offering innovative perspectives on the practical applications of the anthropocentric paradigm, particularly in the domains of education and cognitive science. By focusing on the role of language in cognitive development, the research opens new avenues for future exploration and provides a critical reassessment of existing linguistic models. This work invites further inquiry into the intersection of language, thought, and cognition, contributing to a deeper understanding of the human mind and its connection to language. Ultimately, the study emphasizes the transformative potential of the anthropocentric approach in reshaping linguistic and educational methodologies.